2016
DOI: 10.1038/srep36243
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of benzo[a]pyrene diol epoxide isomers with human serum albumin: Site specific characterisation of adducts and associated kinetics

Abstract: Carcinogenicity of benzo[a]pyrene {B[a]P, a polycyclic aromatic hydrocarbon (PAH)} involves DNA-modification by B[a]P diol epoxide (BPDE) metabolites. Adducts to serum albumin (SA) are not repaired, unlike DNA adducts, and therefore considered advantageous in assessment of in vivo dose of BPDEs. In the present work, kinetic experiments were performed in relation to the dose (i.e. concentration over time) of different BPDE isomers, where human SA (hSA) was incubated with respective BPDEs under physiological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In the early work by Tannenbaum et al, it was shown that (−)-anti enantiomer of BPDE binds to N τ in His in SA [7] and that (+) and (−) enantiomers of anti-BPDE exhibit different reactivity towards the nucleophilic sites in SA [8,13]. We have shown in vitro that (+)-anti-BPDE as well as (+/−)-syn-BPDE form adducts to His in SA [20,21]. It has earlier been shown that the (+)-anti enantiomer of BPDE is the most tumorigenic metabolite [13,22].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…In the early work by Tannenbaum et al, it was shown that (−)-anti enantiomer of BPDE binds to N τ in His in SA [7] and that (+) and (−) enantiomers of anti-BPDE exhibit different reactivity towards the nucleophilic sites in SA [8,13]. We have shown in vitro that (+)-anti-BPDE as well as (+/−)-syn-BPDE form adducts to His in SA [20,21]. It has earlier been shown that the (+)-anti enantiomer of BPDE is the most tumorigenic metabolite [13,22].…”
Section: Introductionmentioning
confidence: 61%
“…From our previous studies, it is indicated that His146 in SA in the two species have similar reactivity. In vitro alkylation with (±)-anti BPDE gives approximately the same adduct levels to His in mouse SA and in human SA, as well as the same ratio (see Section 2.3) of adduct levels from (+)-and (−)-anti-BPDE [20,21]. Further, the peptide sequence in SA close to His146 is identical in the two species, which indicates there is no large difference in the adduct forming capacity of His 146 [21].…”
Section: In Vivo Serum Albumin Samples From Mice and Humansmentioning
confidence: 68%
See 2 more Smart Citations
“…We estimated that 30 ± 6% of the B a P was removed from the solution just by 1h settling and 57 ± 11% by 1h centrifugation. This could highlight the incomplete dissolution but also to the chemical instability of B a P in these abiotic conditions related to its high affinity for serum components (i.e., as albumin in Ferticult ® ) [ 47 , 48 , 49 , 50 ]. UV-vis spectrometry was used to estimate the affinity of B a P for the surface of the aged CeO 2 NMs in abiotic conditions.…”
Section: Methodsmentioning
confidence: 99%